2017
DOI: 10.1074/jbc.m116.755082
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine Cells of the Prostate Derive from the Neural Crest

Abstract: The histogenesis of prostatic neuroendocrine cells is controversial: a stem cell hypothesis with a urogenital sinus-derived progeny of all prostatic epithelial cells is opposed by a dual origin hypothesis, favoring the derivation of neuroendocrine cells from the neural crest, with the secretory and basal cells being of urogenital sinus origin. A computer-assisted 3D reconstruction was used to analyze the distribution of chromogranin A immunoreactive cells in serial sections of human fetal prostate specimens (g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 38 publications
(55 reference statements)
0
23
0
Order By: Relevance
“…(Signoretti et al, 2005) Continued origin (Johansson et al, 2015;Song et al, 2012). However, descriptive analyses have revealed that cells positive for chromogranin A, which marks neuroendocrine cells, can migrate into the UGS during development, suggesting that prostate neuroendocrine cells are derived from the neural crest ectoderm (Aumüller et al, 1999(Aumüller et al, , 2001; notably, this conclusion has been supported by a recent lineage-tracing study (Szczyrba et al, 2017). Thus, additional work will be required to clarify these apparent discrepancies concerning the origin of prostate neuroendocrine cells.…”
Section: Smomentioning
confidence: 51%
“…(Signoretti et al, 2005) Continued origin (Johansson et al, 2015;Song et al, 2012). However, descriptive analyses have revealed that cells positive for chromogranin A, which marks neuroendocrine cells, can migrate into the UGS during development, suggesting that prostate neuroendocrine cells are derived from the neural crest ectoderm (Aumüller et al, 1999(Aumüller et al, , 2001; notably, this conclusion has been supported by a recent lineage-tracing study (Szczyrba et al, 2017). Thus, additional work will be required to clarify these apparent discrepancies concerning the origin of prostate neuroendocrine cells.…”
Section: Smomentioning
confidence: 51%
“…Analysis of the data on the morphogenesis of the lymphoid structures of the prostate indicates that they develop as peripheral organs of the immune system and participate in both local and general immune reactions. Carrying out a detailed study of the development of lymphoid structures of the prostate of rats in normal and after exposure to the antigen, due to the need to confirm the characteristics of the organization and function of the lymphoid formations of the prostate of a human, revealed by them, their connection with histogenetic processes in the prostate, as well as to determine the genesis factors of lymphoid apparatus prostate [21,24,27].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the origin of prostate neuroendocrine cells during organogenesis has not been completely resolved. Although several studies have supported an epithelial origin of neuroendocrine cells (Goldstein et al 2008;Ousset et al 2012), there have also been reports that neuroendocrine cells arise from the caudal neural crest (Szczyrba et al 2017). The basis for these discrepant results remains unclear.…”
Section: Cell Type Specification During Prostate Organogenesismentioning
confidence: 99%